Athlete resilience trajectories across competitive training: the influence of physical and psychological stress - Barczak-Scarboro, N. E.; Kroshus, E.; Pexa, B.; Mihalik, J. K. R.; DeFreese, J. D. (Journal of Clinical Sport Psychology, 2024)
Competitive sport involves physical and psychological stressors, such as training load and stress perceptions, that athletes must adapt to in order to maintain health and performance. Psychological resilience, one`s capacity to equilibrate or adapt affective and behavioral responses to adverse physical or emotional experiences, is an important topic in athlete training and performance. The study purpose was to investigate associations of training load and perceived sport stress with athlete psychological resilience trajectories. Sixty-one collegiate club athletes (30 females and 31 males) completed self-reported surveys over 6 weeks of training. Athletes significantly differed in resilience at the beginning of competitive training. Baseline resilience differences were associated with resilience trajectories. Perceived stress and training load were negatively associated with resilience. Physical and psychological stressors had a small but statistically significant impact on resilience across weeks of competitive training, indicating that both types of stressors should be monitored to maintain athlete resilience.